Catalytic Cyclocodimerization of Silicon-Containing 1,2-Dienes with 1,3,5-Cycloheptatriene in the Synthesis of Biologically Active Bicyclo[4.2.1]Nona-2,4-Dienes - Gulnara N. Kadikova (Chemistry Proceedings, 2024)
The [6+2] cycloaddition of (2-butyl-2,3-butadienyl)(trimethyl)silane and 2,3-butadienyl(trimethyl)silane to 1,3,5-cycloheptatriene was studied using titanium- and cobalt-containing multicomponent catalytic systems: R2TiCl2-R’nAlCl3-n (R = acac, PriO, ButO, Cl; R’ = Et, Bui, n = 2, 3) and CoX2(Y)/Z/ZnI2 (X = acac, Br, I, Cl, OAc; Y = dppe, dppm, dppp, dppb, Ph3P, P(OPri)3, P(OPh)3; Z = Zn, Mg, In, Bu4NBH4). The work investigated the influence of the nature of the central atom of the catalyst, the ligand environment of the catalyst, the nature of the organoaluminum cocatalyst, the reducing agent, the effect of temperature, as well as the nature of the solvent on the yield and stereoselectivity of the formation of cycloadducts. Catalytic cyclocodimerization occurs with the formation of silicon-containing bicyclo[4.2.1]nona-2,4-dienes, which are of interest as promising precursor compounds in the synthesis of new drugs. It is known that many bridged carbo- and heterocarbocyclic compounds containing silicon atoms in the structure have diverse biological activities and are valuable drugs. Based on this, the work for the first time carried out a comprehensive study of the antitumor activity of synthesized silicon-containing bicyclo[4.2.1]nona-2,4-dienes in vitro using various tumor cell lines (U937, K562, Jurkat, HL60) and normal fibroblasts.